Clinical Features and Outcomes of Complementary and Alternative Medicine Induced Acute Liver Failure and Injury. (July 2016) - Hillman, Luke; Gottfried, Michelle; Whitsett, Maureen; Rakela, Jorge; Schilsky, Michael; Lee, William M; Ganger, Daniel
Abstract : OBJECTIVES: The increasing use of complementary and alternative medicines (CAMs) has been associated with a rising incidence of CAM‐induced drug‐induced liver injury (DILI). The aim of this study was to examine the clinical features and outcomes among patients with acute liver failure (ALF) and acute liver injury (ALI) enrolled in the Acute Liver Failure Study Group database, comparing CAM‐induced with prescription medicine (PM)‐induced DILI. METHODS: A total of 2, 626 hospitalized patients with ALF/ALI of any etiology were prospectively enrolled between 1998 and 2015 from 32 academic transplant centers. Only those with CAM or PM‐induced ALI/ALF were selected for analysis. RESULTS: A total of 253 (9.6%) subjects were found to have idiosyncratic DILI, of which 41 (16.3%) were from CAM and 210 (83.7%) were due to PM. The fraction of DILI‐ALF/ALI cases due to CAM increased from 1998–2007 to 2007–2015 (12.4 vs. 21.1%, P =0.047). There was no difference in the type of liver injury—hepatocellular, cholestatic, or mixed—between groups as determined by R score ( P =0.26). PM‐induced DILI showed higher serum alkaline phosphatase levels compared with the CAM group (median IU/L, 171 vs. 125, P =0.003). The CAM population had fewer comorbid conditions (1.0 vs. 2.0, P <0.005), higher transplantation rates (56 vs. 32%, P <0.005), and a lower ALF‐specific 21‐day transplant‐free survival (17 vs. 34%, P =0.044). CONCLUSIONS: CAM‐induced DILI is at least as severe in presentation as that observed due to PM with higher rates of transplantation and lower transplant‐free survival in those who progress to ALF. This study highlights the increasing incidence of CAM‐induced liver injury and emphasizes the importance of early referral and evaluation for liver transplantation when CAM‐induced liver injury is suspected.